PRELIMINARY TECHNICAL ASSESSMENT OF WATER DISTRIBUTION NETWORKS - Tuhovčák, Ladislav; Tauš, Miloslav; Sucháček, Tomáš (Czech Journal of Civil Engineering, 2015)
The knowledge of the current technical condition of the operated system is in the interest of the owner or operator of public water supply systems. Such information is the starting point when making decisions on investment projects or planning water mains renewal. The submitted paper introduces the methodology of preliminary assessment of the technical condition of water supply systems and outputs of the software application TEA Water, which makes it possible to assess the technical condition of the specific elements of the water supply systems and clear displaying with the presentation of the assessment results for the entire considered water supply system.